(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A factorial experiment was conducted at the Agriculture fields of Diyala University on alluvial mixed soils in spring 2021 according to the complete random sector (R.C.B.D.) design to study the effects of two dates of pinching as well as the comparative treatments(without pinching, 15 and 40) days, after planting and spraying with zinc by two concentrations with non –spraying treatment (300, 150 and 0). Ppm. On castor plant (Ricinus communis L.).The results obtained revealed the following :the process of developing apex pinching of the plant (first pinching) significantly exceeded In the average quality of the seed yield in plant and hectare and the ratio and yield of oil amounted to 53.55 g, 1115.0 kg.h-1, 36.1%, 402.7 kg.h-1 respectively, In addition, it increased the average total percentage of unsaturated fatty acids in the oil to 37.73%. treatment of spraying with zinc at a concentration of 300 ppm showed significant superiority of the average seed yield, characteristic of plant, hectare and oil yields, reaching 52.93 g and 1102.6 kg. h-1, 388.3 kg. h-1-, respectively, increasing the average oil and total percentage of unsaturated fatty acids to 35.5% and 32.72%, respectively. In addition to the role of zinc application at 150 ppm concentration. The overlap of the two test factors (first pinching with spraying with zinc at 300 ppm concentration) had a significant impact on the quality of seed yield in plants, hectares, and oil yield, 56.89 g, 1184.8 kg.h-1, 427.2 kg.h-1. continuous.